ANALISIS KEGIATAN CUSTOMER RELATIONSHIP MANAGEMENT MELALUI MEMBERSHIP CARD UNTUK MENINGKATKAN LOYALITAS KONSUMEN: STUDI KASUS PADA SOGO PREMIER CARD - Wibowo Soedjono; Frendy Limantoro (President University, 2018)
Abstract. Competition in various industries in Indonesia is getting tighter. Various companies are competing to be at the forefront of the minds of consumers. Strategy for strategy is implemented, one of them is Customer Relationship Management (CRM) strategy conducted by PT. Panen Lestari Internusa by launching Sogo Premier Card as a form of membership card for its customers. This research is a research with a qualitative approach that analyzes how CRM strategies are implemented by PT. Panen Lestari Internusa. The interview technique used was a semi-structured interview with two internal speakers from PT. Panen Lestari Internusa and four external informant whom are SPC members and two marketing communication expertise. Data analysis techniques in this study used coding techniques with reliability checking techniques using source triangulation. The results showed that the use of Sogo Premier Card as a form of CRM was considered to help increase the loyalty of Sogo Department Store consumers with three important elements such as reward based bonds, selection and interaction.Keywords: customer relation management, consumer loyalty, membership card